Renewable Energy in China - V. I. Salygin; I. A. Guliyev; M. I. Ryabova (Vestnik MGIMO-Universiteta)
China is the most densely populated country in the world with high rate of economic growth resulting in higher demand for energy resources and in strive to guarantee stable supply of these resources. Chinese annual GDP growth in 2012 and 2013 was down to 7.7% comparing to 10% in 2000-2011 [7]. In 2012 and 2013 economic growth stumbled because of slowdown in manufacturing and exports, taking into account that Chinese government was eager to cut inflation and excessive investments in some segments of the market. Speaking about energy sector Chinese government is aimed at promotion of market-based pricing systems, activities for advanced energy efficiency and higher competition between energy companies, and increased investment in renewable energy resources. Considering renewables as one of many ways to diversify energy supplies, lower dependence on coal and improve environmental situation Chinese government actively supports and develops programs aimed at support of renewable energy industry in China. Chinese economic development is tightly attached to five-year plans. It seems important to mention the fact that main energy goals for current 12-th "five-year plan" are to achieve 15% renewables consumption and CO2 sequestration up to 40-45% by2020 in order to lower dependency on coal and improve environmental situation. As a result of Chinese state policy to develop renewables China achieved certain results in wind energy, helioenergetics, hydroenergetics and energy from waste recycling.